MARKETING EFFICIENCY OF BALI PIG IN ORDER TO INCREASE FARMERS’ INCOME IN THE MARGINAL REGION - I W., Sukanata; Parimartha, I K. W.; Putri, B. R. T. (Majalah Ilmiah Peternakan; Vol 22 No 3 (2019): Vol. 22 No.3 (2019)DO - 10.24843/MIP.2019.v22.i03.p05, 2019)
The research was conducted in Gerokgak, Abang, and Nusa Penida Districth from June to October 2018, with the aims to determine the marketing efficiency of bali pig. Types of data used were quantitative and qualitative data, which were sourced from the primary data. Data were collected through observation, interviews, and documentation. Interviews was conducted with 100 farmers, 20 middleman consisting of 5 “penyotek (informant)”, 5 “pengepul (collectors)”, 5 inter-regional traders, and 5 grilled pig producers. The marketing efficiency were determined by market structure, marketing chanel, farmer’s share, marketing margin, and profit cost ratio. The results of this study indicate that the marketing system of bali pig is less efficient. There are four chanels in bali cattle marketing with imperpectly market structure (oligopsony). Average of the farmer’s share from the fourt chanels are 61,41%. While the marketing margin of the marketing agencies were uneven with the range of 0,94%-37,5% of the consumer price. The profit-cost ratio achieved by the marketing agencies are 172,73% - 700%, however, that achieved by farmers are an average of only 48.43%.